Genetic variability and association studies for yield and pre-harvest sprouting traits in greengram [Vigna radiata (L.) Wilczek] - P. J. S. Pramod1*, N. Hari Satyanarayana2, J. Sateesh Babu2, K. Jaya Lalitha3 and V. Roja4 (Electronic Journal of Plant Breeding)
The present study investigates the genetic variability and associations of agronomic traits impacting pre-harvest sprouting (PHS) in 30 greengram genotypes. Significant variability was observed across multiple traits, with seed yield per plant ranging from 2.19 to 7.82 g. ​Key findings indicate that hard seed percentage and alpha-amylase activity at different germination intervals are having high heritability, demonstrating genetic heritability essential for breeding strategies.​ High phenotypic variability suggests environmental influence on trait expression, especially in traits such as days to maturity and pod diameter. Correlation analysis revealed robust positive associations between seed yield and days to maturity, while negative correlations were noted with epicuticular wax content and pod wall thickness. The path analysis identified that days to 50 % flowering, along with alpha-amylase activity, directly affects yield, emphasizing the intricacies of trait interrelationships. This research aims to contribute towards developing PHS-resistant mung bean varieties that enhance crop yield and quality.